PERLINDUNGAN HAK BAGI PEMOHON KEPUTUSAN TATA USAHA NEGARA AKIBAT PERMOHONAN FIKTIP POSITIF DI PENGADILAN TATA USAHA NEGARA DENPASAR - Kristiawan, Gede Budi; Sugiantari, Anak Agung Putu Wiwik; Sudirga, I Made (Fakultas Hukum Universitas Ngurah Rai, 2024)
Dispute resolution procedures from lawsuits and applications filed at the State Administrative Court based on negative fictitious administrative orders or positive fictitious administrative orders. The adoption of the positive fictitious principle in various legislative policies of member states has finally brought positive results in facilitating the process of obtaining licenses and issuing decisions / other actions submitted by citizens to administrative organs. The essence of the Positive Fictitious Principle is that 'silence means agreement' and aims for legal certainty. The requirements of the application must have been received in full and are associated with legal principles that are affected to be the reason for not needing the involvement of the judiciary. On the other hand, the court is needed to provide legal protection for third parties who feel aggrieved by the issuance of decisions born from the positive fictitious process.